Aspect-oriented programming with the e verification language : - Robinson, David (Elsevier/Morgan Kaufmann, 2007)
Aspect-Oriented Programming with the e Verification Language takes a pragmatic, example based, and fun approach to unraveling the mysteries of AOP.